Community Identity and Resilience as a Psychological Response to Converts on the Aceh Border - Al-Fairusy, Muhajir; Rohana, Syarifah; Kurniawan, Cecep Soleh; Hemay, Idris; Budiman, Zulfatmi (International Journal of Islamic Educational Psychology, 2024)
It cannot be denied that since Aceh implemented Islamic Sharia as the main discourse of identity for this province, there have been cultural clashes between communities with different beliefs, especially in Aceh border areas such as Singkil Regency. This social problem has incited the emergence of the identity of converting to Islam for some people on the Aceh border, especially those who come from Nias and Pakpak. This study is an attempt to understand and explain the existence of the Muslim community on the Aceh border using the concepts of social identity and community resilience. This study was carried out due to a lack of studies on groups of converts who are influenced by sociopolitical conditions, not just psychological-spiritual experiences, as in several previous studies that looked at the phenomenon of religious conversion. The phenomenon of converting to Islam on the Aceh border was triggered by social identity and survival strategies among the majority by negotiating identity as a convert. This descriptive research applied a grounded research approach and a cultural paradigm. Data collection techniques began with library research, observation, and interviews with several informants related to research data. The results of the research showed that social identity as a convert to Islam at the border cannot be read as limited to religious conversion due to belief but rather as an effort to negotiate social identity as a form of psychological resilience of the community in responding to the dynamics and socio-religious problems in the Aceh border community.